ANALISIS PENGGUNAAN QRIS OLEH WISATAWAN ASING PADA UMKM LOKAL BATAM - Nainggolan, Nora Pitri; Heryenzus, Heryenzus; Situmorang, Robert (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2026)
Batam City has a strategic position as the homepage of Indonesia's economy that borders Singapore and Malaysia, making it a dynamic hub for international transactions. This study aims to analyze the use of the Quick Response Code Indonesian Standard (QRIS) by foreign tourists on local MSMEs in Batam and its impact on entrepreneurial efficiency. Using a descriptive qualitative approach with the Technology Acceptance Model (TAM) theoretical framework, data were collected through participatory observation and in-depth interviews in shopping malls and culinary centers in the Nagoya and Batam Centre areas. The results show that the Cross-border QR feature has increased the shopping preferences of foreign tourists because it provides real-time currency conversion convenience and transaction security. Field findings confirm that perceived usefulness and perceived ease of use are key factors driving the adoption of this technology. Although network infrastructure constraints are still found at some points, the implementation of QRIS has been proven to increase the daily turnover of MSMEs by an average of 15-25% and strengthen the competitiveness of local entrepreneurs in the regional digital economy ecosystem. This study recommends the need to strengthen digital literacy for business actors to optimize the potential of international markets in border areas.